2019
DOI: 10.1021/acsami.9b10622
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intrinsic Flexibility on Adsorption Properties of Metal–Organic Frameworks at Dilute and Nondilute Loadings

Abstract: Molecular simulation of adsorption in nanoporous materials has become a valuable complement to experimental studies of these materials. In almost all cases, these simulations treat the adsorbing material as rigid. We use molecular simulations to examine the validity of this approximation for the adsorption in metal–organic frameworks (MOFs) that have framework flexibility without change in their unit cells because of thermal vibrations. All nanoporous materials are subject to this kind of framework flexibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(93 citation statements)
references
References 60 publications
7
83
3
Order By: Relevance
“…Fully flexible simulations are required to evaluate their potential, 33,34 and therefore would have remained undiscovered from rigid screening studies, for which there are very few exceptions. 35,36 Third, one must find an adsorbent that mimics the idealized flexible slit pore model as closely as possible in order to maximize deliverable capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fully flexible simulations are required to evaluate their potential, 33,34 and therefore would have remained undiscovered from rigid screening studies, for which there are very few exceptions. 35,36 Third, one must find an adsorbent that mimics the idealized flexible slit pore model as closely as possible in order to maximize deliverable capacity.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 It should be noted that such materials could only ever be computationally identified with a fully flexible treatment coupling framework dynamics and adsorption; 16,[31][32][33][34] hence, they will have remained hidden from almost any high-throughput adsorbent screening study to date. 35,36 Finally, we show that the isoreticular tunability 37,38 of metal-organic frameworks (MOFs) can be used to design an improved version of the M(NDC) adsorbent. Ultimately, this work outlines a path forward to discover deliverable capacity materials through concrete design strategies motivated by the models and simulations developed herein.…”
Section: P [Bar]mentioning
confidence: 99%
“…Recent studies have shown that the importance of intrinsic flexibility arising from thermal vibrations varies considerably for MOFs depending on the adsorption property of interest. 206 , 207 For example, it was shown that intrinsic flexibility can be more important where pore sizes are comparable to the kinetic diameter of adsorbate molecules. 206 , 208 For zeolites, however, the effect of thermal framework vibrations on molecular adsorption was shown to be negligible and the rigid framework assumption can be reliably used in GCMC simulation for these materials.…”
Section: Multiscale Screening Workflowmentioning
confidence: 99%
“… 206 , 207 For example, it was shown that intrinsic flexibility can be more important where pore sizes are comparable to the kinetic diameter of adsorbate molecules. 206 , 208 For zeolites, however, the effect of thermal framework vibrations on molecular adsorption was shown to be negligible and the rigid framework assumption can be reliably used in GCMC simulation for these materials. 209 For simulation of flexible materials that undergo significant changes in unit cell volume, more advanced simulation methods such as the osmotic ensemble and Gibbs ensemble Monte Carlo should be used.…”
Section: Multiscale Screening Workflowmentioning
confidence: 99%
“…29,30 It should be noted that such materials could only ever be computationally identified with a fully flexible treatment coupling framework dynamics and adsorption; 16,[31][32][33][34] hence, they will have remained hidden from almost any high-throughput adsorbent screening study to date. 35,36 Finally, we show that the isoreticular tunability 37,38 of metal-organic frameworks (MOFs) can be used to design an improved version of the M(NDC) adsorbent. Ultimately, this work outlines a path forward to discover deliverable capacity materials through concrete design strategies motivated by the models and simulations developed herein.…”
Section: Introductionmentioning
confidence: 99%